Metode MCDA Untuk Pengukuran Tingkat Kesadaran Keamanan Informasi Pada Mahasiswa - Dafid .; Dorie Pandora Kesuma (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2020)
In a higher education institution, it is certainly common for students to carry out various academic and non-academic activities using information technology. Awareness of information security is one of the substantial factors in the utilization of these technologies. With low level of awareness, information security incidents will be arising. This research measures the level of information security awareness of STMIK XYZ students. The purpose of this research is to determine the level of information security awareness of students so that actions can be determined that need to be taken to improve low awareness and maintain what is already good. This research using Multiple Criteria Decision Analysis (MCDA) method. The results showed that information security awareness's level of STMIK XYZ students is "average" (score:71%). From three dimensions that measured, there is only one dimension that at "poor” level(behavior dimension). From six measurement areas, three measurement areas; policies, mobile equipment, and consequences are at a poor level. These results indicate that some actions required to improve information security awareness's level of STMIK XYZ students.